Effect of Natural Enemy (Chrysoperla carnea Stephens) against Sucking Insect Pests of Okra - Ali, Syed Shahzad; Ahmed, Syed Sohail; Rizwana, Huma; Ahmed, Ali; Khoso, Abdul Ghaffar; Mureed, Paras; Mureed, Sumbel; Meano, Falak Naz; Ibrahim Mengal, Muhammad; Shahwani, Shahid Ali (Journal of Basic & Applied Sciences, 2017)
An experiment effect of natural enemy (Chrysoperla carnea Stephens.) against sucking insect pests of Okra was carried out at Latif Farm, Sindh Agriculture University, Tando Jam during 2014.The results showed that overall maximum mean population of jassids (1009.5 ± 78.12/plant) was recorded in pre-treatment treated plot followed by thrips (706.17 ± 34.26/plant), mites (572.5± 33.00/plant) and whiteflies (209.83 ± 19.76/plant) respectively. Whereas, the overall maximum mean population of jassids (1322.44 ± 8.6/plant6) was recorded in pre-treatment control plot, followed by thrips (828.05 ± 6.77/plant), mites (640.55 ± 5.95/plant) and whiteflies (267.38 ± 4.74/plant) respectively. However, the overall maximum mean of jassids (434.27 ± 4.91/plant) were recorded in post-treatment control plot, followed by thrips (278.11 ± 3.93/plant), mites (134.11 ± 2.63/plant) and whiteflies (18.83 ± 0.99/plant), respectively. The results further revealed that the statistical analysis of data through paired T-test between treated and control plot of jassids, whiteflies, thrips and mites showed significantly different at (P<0.05) level. Whereas, the statistical analysis of data through paired T-test between pre-treatment and post-treatment of jassids, whiteflies, thrips and mites also showed significantly different at (P <0.05) level.